A DATA HIDING SCHEME BASED ON CHAOTIC MAP AND PIXEL PAIRS - Dogan, Sengul (Assoc Digital Forensics, Security & Law, 2017)
Information security is one of the most common areas of study today. In the literature, there are many algorithms developed in the information security. The Least Significant Bit (LSB) method is the most known of these algorithms. The LSB method is easy to apply; however, it is not effective on providing data privacy and robustness. In spite of all its disadvantages, LSB is the most frequently used algorithm in literature, due to providing high visual quality. In this study, an effective data hiding scheme alternative to LSB, 2LSBs, 3LSBs and 4LSBs algorithms (known as xLSBs), is proposed. In this method, random numbers which are to be used as indices of pixels of the cover image are obtained from chaotic maps and data hiding process is applied on the values of these pixels by using modulo function. Calculated values are embedded in cover image as hidden data. Success of the proposed data hiding scheme is assessed by Peak Signal-to-Noise Ratio (PSNR), payload capacity and quality.
Keywords: Image Authentication; Steganography; Watermarking; Block